GREBEK STUNTING PROGRAM IN ACCELERATE STUNTING DECREASE IN BULUKUMBA DISTRICT - Fadilahaya, Andi Aqila; Sakawati, Herlina; Yamin, Muh Nur; Sulmiah, Sulmiah (Universitas Negeri Makassar, 2025)
Stunting is a failure during the growth period of children which is one of the government's concerns. This study aims to determine the implementation of the Grebek Stunting Program in Accelerating Stunting Reduction and the Role of Stakeholders in Bulukumba Regency, in this study using study aids from David C Korten, namely Program Suitability with Utilizers, Suitability of Implementing Organizations with Utilizers, and Suitability between Beneficiary Groups and Implementing Organizations. This type of research is qualitative research with data collection techniques, namely observation, interviews, and documentation. The data obtained from the results of the study were processed using the interactive model data analysis technique of Miles, Huberman and Saldana (2014). Variables in interactive model data analysis techniques include: Data Collection, Data Condensation, Display Data, Conclusion. The results of the study show that the implementation of the Grebek Stunting Program and the Role of Stakeholders in Bulukumba Regency are in the category of good when viewed from several indicators, namely: Program Suitability with Utilizers, Suitability of Implementing Organizations with Utilizers, and Suitability between Beneficiary Groups and Implementing Organizations. The Bulukumba Regency Government has succeeded in reducing the stunting rate even though there are still cases due to limited knowledge, food quality and community nutrition and budget limitations in providing comprehensive interventions